Etika Komunikasi Islam Dalam Dakwah Koh Dennis Lim Di Media Sosial Tiktok - Tri Wahyuni Pebirawati (Institut Agama Islam (IAI) Nurul Hakim, 2023)
Da'wah is an obligation for every Muslim, every Muslim who is a mulatto is required to carry out Islamic orders, namely advising one another and spreading goodness among others. In society, the spread of Islam is carried out in mosques and delivered by preachers using traditional methods. However, along with the development of technological devices, various ways of studying Islam have emerged and the methods of preaching that have been carried out have also developed rapidly. This study seeks to analyze the ethics of Islamic communication by young preachers who are much loved by teenagers. The presence of young preachers, from various educational backgrounds and experiences is interesting to analyze, one of these factors is that preachers from social media channels are no longer fixated on strict rules such as in-depth Islamic educational background, and understanding of classic books. But more on the content of the delivery which makes it easy for the object to understand Islam more easily and be able to solve today's problems well.